Public-private partnership: Physical, social, and human infrastructure in the Philippines - Ernesto M. Pernia; Marianne C. Sales (University of the Philippines, School of Economics (UPSE), 2023)
Partnership between the public and private sectors, the main constituents of the economy, is not only logical but seems like a natural institutional arrangement. It can be a symbiotic relationship which brings about mutually beneficial processes and outcomes that redound to the economy and society-at-large. Among the three types of infrastructures, human is evidently the most vital and of the highest priority, followed by social infrastructure which directly undergirds human development that begins in the womb, and physical infrastructure required to buttress the country's social and economic growth sustainably. This essay discusses physical infrastructure at length followed by human capital and social infrastructure.
Keywords: 330; Öffentlich-private Partnerschaft; Philippinen